Oral clobazam compared with diazepam in recurrent febrile seizures in pediatric patients: compliance and effectiveness - Khanum, Mafuza; Baby, Momotaz Jahan; Anwar, S. Serjina; Akter, Nasima; Afroze Jui, Farjana; Binta Shamim, Kazi Farhana; Khandokar, Sumona; Akhter Banu, Nazneen (International Journal of Contemporary Pediatrics, 2025)
Background: Febrile seizures (FS), affecting 2–5% of children under five, often recur and impact families emotionally. This study aims to assess the compliance and effectiveness of oral Clobazam versus Diazepam in treating recurrent FS in children. The aim of the study was to evaluate the compliance and effectiveness of oral Clobazam compared to Diazepam in pediatric patients with recurrent FS. Methods: This comparative observational study was conducted at the Department of Pediatrics, Sir Salimullah Medical College Mitford Hospital (SSMCMH), Dhaka, over a 12 months period. One hundred children aged 6 months to 5 years with FS were randomized into Group A (oral Diazepam) with 51 children and Group B (oral Clobazam) with 49 children. The study was ethically approved and data were analyzed using SPSS 20 and Excel 2007 with t-Tests at p=0.05. Results: In a study of 100 pediatric patients (Group A: 51, Group B: 49), males were more common in both groups (32.79% in Diazepam, 26.23% in Clobazam) and most children were aged 6–24 months (29.5% vs. 32.78%). Seizures occurred in 3.92% (Diazepam) and 8.16% (Clobazam), with no significant difference (p>0.05). Non-compliance and recurrent seizures were slightly higher in the Clobazam group. Side effects included irritability (Diazepam) and vomiting, drowsiness and irritability (Clobazam). Conclusions: This study found that oral Clobazam and Diazepam have similar efficacy and compliance, with Clobazam showing a slightly higher incidence of recurrent seizures and side effects.